PENGEMBANGAN VIDEO PEMBELAJARAN PADA MATERI KESETIMBANGAN DAN DINAMIKA ROTASI MENGGUNAKAN APLIKASI ADOBE FLASH - Radiannita Tri Rahayu; Y Yennita Y Yennita; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : Physics is a subject that is less attractive to high school students in general, this is due to the lack of applications of physics in everyday life, especially in the matter of equilibrium and rotational dynamics. Therefore, the purpose of this study was to develop a video lesson on the subject of equilibrium and class rotation dynamics using a valid Adobe Flash application. The type of research used is Research and Development (R&D) using the ADDIE model which consists of five stages, namely: analysis, design, development, implementation and evaluation. At the analysis stage, several analyzes were carried out including needs analysis, curriculum analysis, and material analysis. At the design stage, the researcher designs a learning video according to the results of the analysis that has been done previously, and designs a validation sheet according to the research aspects. At the development stage, media development in the form of learning videos was carried out to the validation stage. The data obtained in the form of the average validation results of three validators. The results of the second stage of validation on all questions in each aspect have received a minimum score of 3. The results showed that the learning video on equilibrium material and class rotation dynamics using the Adobe Flash application met the valid criteria from the content aspect, the learning media aspect, and the linguistic aspect. So it can be concluded that the learning video on equilibrium material and class rotation dynamics using the Adobe Flash application is valid and feasible to use in the learning process.Key words: Learning Video, Adobe Flash, Equilibrium and Rotation Dynamics